2021
DOI: 10.1002/lim2.47
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low medication adherence in patients with Type 2 diabetes mellitus attending a tertiary hospital in Bangladesh

Abstract: Background: Adherence to prescribed medication is essential for glycemic control and to delay the onset of complications. However, information on medication adherence among patients with Type 2 diabetes mellitus is sparse in Bangladesh. This study aimed to determine medication adherence and factors associated with low adherence in patients with Type 2 diabetes in Bangladesh. Methods: A cross-sectional study was conducted among 500 consecutive patients with Type 2 diabetes attending a tertiary hospital in Bangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Patients with T2D may have hypertension for years prior to the onset of overt diabetes. Furthermore, people with diabetes have shown low medication adherence in Bangladesh, which exposes them to increased risks of diabetes complications [ 40 , 41 , 42 ]. Still, if BP rises further, these patients are subsequently likely to develop CKD and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2D may have hypertension for years prior to the onset of overt diabetes. Furthermore, people with diabetes have shown low medication adherence in Bangladesh, which exposes them to increased risks of diabetes complications [ 40 , 41 , 42 ]. Still, if BP rises further, these patients are subsequently likely to develop CKD and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In another study in Botswana, the prevalence of low medication adherence of anti-diabetic medications was 41.8% among patients with T2DM. 10 In 2021, Islam et al 11 reported a prevalence of low medication adherence of 48.2% among patients with T2DM in Bangladesh. Low medication adherence is indeed a devastating problem in patients with T2DM and studies have shown that the problem usually increases with the duration after treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The studies deployed different methods and designs to collect insights on illness perception and medication adherence in adult patients with T2DM. The scoping includes 20 quantitative studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Among the quantitative research, we found one randomized controlled trial (RCT) and two retrospective studies, while the remaining were cross-sectional studies.…”
Section: Findings/resultsmentioning
confidence: 99%
“…Therefore, the context and circumstances of adult patients shape their uptake of medications and treatment. In the study conducted by Islam et al (2021) [ 22 ], the factors influencing T2DM patients’ medication adherence were evaluated, and it was found that 46.3% of 2070 patients had suboptimal levels of medication adherence. The mean age of the participants was 50.2 ± 10.2 years (56.2% females).…”
Section: Discussionmentioning
confidence: 99%